Plasmonic nanorod probes' journey inside plant cells for in vivo SERS sensing and multimodal imaging. Issue 13 (16th March 2023) - Cupil-Garcia, Vanessa; Li, Joy Q.; Norton, Stephen J.; Odion, Ren A.; Strobbia, Pietro; Menozzi, Luca; Ma, Chenshuo; Hu, Jianhong; Zentella, Rodolfo; Boyanov, Maxim I.; Finfrock, Y. Zou; Gursoy, Doga; et al.
Abstract : Plasmonic silver-coated nanorods were demonstrated to enter plant cells using a multimodal imaging approach. Surface-Enhanced Raman Scattering spectra from dye-coated nanorods were acquired in vivo from whole plant leaves treated with nanorods. Abstract : Nanoparticle-based platforms are gaining strong interest in plant biology and bioenergy research to monitor and control biological processes in whole plants. However, in vivo monitoring of biomolecules using nanoparticles inside plant cells remains challenging due to the impenetrability of the plant cell wall to nanoparticles beyond the exclusion limits (5–20 nm). To overcome this physical barrier, we have designed unique bimetallic silver-coated gold nanorods (AuNR@Ag) capable of entering plant cells, while conserving key plasmonic properties in the near-infrared (NIR). To demonstrate cellular internalization and tracking of the nanorods inside plant tissue, we used a comprehensive multimodal imaging approach that included transmission electron microscopy (TEM), confocal fluorescence microscopy, two-photon luminescence (TPL), X-ray fluorescence microscopy (XRF), and photoacoustics imaging (PAI). We successfully acquired SERS signals of nanorods in vivo inside plant cells of tobacco leaves. On the same leaf samples, we applied orthogonal imaging methods, TPL and PAI techniques for in vivo imaging of the nanorods. This study first demonstrates the intracellular internalization of AuNR@Ag inside whole plant systems for in vivo SERS analysis in tobacco cells. This work demonstrates the potential of this nanoplatform as a new nanotool for intracellular in vivo biosensing for plant biology.